1985
DOI: 10.2307/2408790
|View full text |Cite
|
Sign up to set email alerts
|

The Quantitative Assessment of Phylogenetic Constraints in Comparative Analyses: Sexual Dimorphism in Body Weight Among Primates

Abstract: We have presented a formal model for the quantitative analysis of phylogenetic and specific effects on the distribution of trait values among species. Total trait values are divided into phylogenetic values, inherited from an ancestral species, and specific values, the result of independent evolution. This allows a quantitative assessment of the strength of the phylogenetic inertia, or burden, displayed by a character in a lineage, so that questions concerning the relative importance of phylogenetic constraint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
346
1
7

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(361 citation statements)
references
References 31 publications
7
346
1
7
Order By: Relevance
“…A detailed description of these metrics can be found elsewhere (Cheverud et al , 1985; Gittleman and Kot, 1990, Diniz-Filho et al 1998; Pagel, 1999; Freckleton et al , 2002; Blomberg et al , 2003). First, for statistical-based metrics, we used the Moran’s I autocorrelation coefficient, which is given by I=(nS0)[i=1nj=1n(yiy¯)(yjy¯)wiji=1n(yiy¯)2]where n is the number of species, y i and y j are the trait values in a vector Y for species i and j ( i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of these metrics can be found elsewhere (Cheverud et al , 1985; Gittleman and Kot, 1990, Diniz-Filho et al 1998; Pagel, 1999; Freckleton et al , 2002; Blomberg et al , 2003). First, for statistical-based metrics, we used the Moran’s I autocorrelation coefficient, which is given by I=(nS0)[i=1nj=1n(yiy¯)(yjy¯)wiji=1n(yiy¯)2]where n is the number of species, y i and y j are the trait values in a vector Y for species i and j ( i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The earliest techniques were based on statistical methods ( e.g. , phylogenetic autocorrelation coefficients, phylogenetic correlograms and autoregressive models), that quantify the level of phylogenetic autocorrelation for a given trait of interest throughout the phylogeny (see Cheverud et al , 1985; Gittleman and Kot, 1990; Diniz-Filho et al , 1998), or under non-stationary processes (Diniz-Filho et al , 2010). When more detailed and accurate phylogenies are available, it is also possible to ascertain the expected divergence between species by assuming a theoretical model of trait evolution, and thus derive model-based metrics to compare expected and observed divergences ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of SSD is slowed by genetic (97), phylogenetic (26), developmental (8), and/or physiological (93) constraints. For example, empirical studies have shown that heritabilities are similar between the sexes and that the between-sex genetic correlations ( r G ) are near 1.0 (because males and females share the same genes that control growth and development) (79, 98, 102).…”
Section: Introductionmentioning
confidence: 99%
“…In the same fashion, many life-history traits "scale" to body mass (Millar 1977;Western 1979;Western and Ssemakula 1982;Peters 1983;Calder 1984;Schmidt-Nielsen 1984;Charnov 1993), and we expected no exception when it comes to egg size. The second problem is that many organismal traits follow a phylogenetic pattern due to shared ancestry of groups of species (e.g., Cheverud et al 1985;Dobson 1985;Felsenstein 1985;Harvey and Pagel 1991;Miles and Dunham 1992). For albatrosses and petrels, these two issues are highly associated because body mass itself follows a strong phylogenetic pattern (network autocorrelation analysis, = 0.800, n = 44, P < 0.0001; Dobson and Jouventin 2010).…”
Section: Methodsmentioning
confidence: 99%